The true self as essentially morally good: An obstacle to virtue development?. Issue 2 (3rd April 2022) - Stichter, Matt
ABSTRACT: Psychological research has revealed that there is a strong tendency for people to believe that they have a 'true self', and to believe that this true self is inherently morally good. This would seemingly be very good news for virtue theorists, since this may help to promote virtue development. While there are some obvious benefits to people having morality intrinsically tied to their sense of self, in this paper I want to suggest instead that there may also be some significant drawbacks, especially when it comes to motivating virtue development and moral improvement. In part this stems from people's belief in their own inherent moral goodness being merely assumed (as part of one's core identity), rather than earned (say through reliably good moral behavior). This disconnection between identity and behavior can result in attempts to reinforce one's identity as morally good, at the expense of virtuous behavior or self-improvement.